Effects of Benazir Income Support Program on Socioeconomic Conditions of Rural Area of District Peshawar (Journal of Asian Development Studies, 2025)
The study was conducted in the rural area of District Peshawar since 2025, with the primary objective of examining the effects of BISP on the socio-economic conditions of its beneficiaries. The total number of respondents was 227, with 47 from Suleman Khel, 45 from Khazana Bala, 63 from Afithozai, and 72 from Afithozai. The pair t-test was used. The mean monthly income of BISP was Rs. 41489, and without BISP, it was Rs.27588. The t-value is 5.526, and the P-value is 0.000. The result is significant, explaining that BISP has increased the monthly income of the respondents. However, the after-program monthly mean expenditure with BISP is Rs. 36179, and without it is Rs.31609. The t-value is 14.934, and the P-value is 0.000. Therefore, the result is highly significant, indicating that BISP has improved the expenditure level of the respondents. Similarly, the monthly savings with BISP was Rs 1939, and without the BISP fund, it was Rs. 4018. The t-value is 16.953, and the P-value is 0.000. The result is highly significant, indicating that the savings after the program were improved. The major problems and constraints faced to women beneficiaries are: fund was not available in time; the cash was less than their requirement; the fund was not available at the door steps; based on problems the study recommend that to provide fund according to their requirement; deliver at their door steps and offer at the proper time to beneficiaries in the study area.